Stress Testing of the Montenegrin Banking System with Aggregated and Bank-Specific Data - Sanja Vuković (Journal of Central Banking Theory and Practice, 2014)
There are many different approaches to the process of stress testing and two of them will be investigated in this paper. The first one is a stress test performed on aggregated data i.e. the banking system as a whole. The variable of interest in both exercises is the Loan Loss Provision ratio (hereinafter: the LLP). The main goal of the thesis is to find an answer to the following question: what are the macroeconomic variables that influence LLP the most and how will LLP, as a variable of interest, behave in a situation when all these variables were to experience negative performance at the same time? The resilience of the banking system to such scenario will be tested through the capital adequacy ratio. In order to find out more about the management practices of banks, microlevel data on banks were also used in the analysis. The focus was to see which of the variables are able to explain the LLP ratio for each bank individually and how is this information helpful for possible improvements in the banking sector. The relations between these variables will be able to explain some of the banks' losses and some of the banks' practices regarding credit activities. The analysis there will provide for some recommendations for the banks but also for the Central Bank and its way to influence the practices in the banking sector.
Keywords: E50; E58; C12; C13; C32; C33; 330; stress testing; loan loss provisions; estimation; credit risk